Molecular epidemiology of group C viruses (Bunyaviridae, Orthobunyavirus) isolated in the Americas - Nunes, Marcio R T; Travassos da Rosa, Amelia P A; Weaver, Scott C; Tesh, Robert B; Vasconcelos, Pedro F C (Journal of virology, 2005)
To date, no molecular studies on group C viruses (Bunyaviridae, Orthobunyavirus) have been published. We determined the complete small RNA (SRNA) segment and partial medium RNA segment nucleotide sequences for 13 group C members. The full-length SRNA sequences ranged from 915 to 926 nucleotides in length, and revealed similar organization in comparison with other orthobunyaviruses. Based on the 705 nucleotides of the N gene, group C members were distributed into three major phylogenetic groups, with the exception of Madrid virus, which was placed outside of these three groups. Analysis of the Caraparu virus strain BeH 5546 revealed that it has an SRNA sequence nearly identical to that of Oriboca virus and is a natural reassortant virus. In addition, analysis of 345 nucleotides of the Gn gene for eight group C viruses and for strain BeH 5546 revealed a different phylogenetic topology, suggesting a reassortment pattern among them. These findings represent the first evidence for natural reassortment among the group C viruses, which include several human pathogens. Furthermore, our genetic data corroborate previous relationships determined using serologic assays (complement fixation, hemagglutination inhibition, and neutralization tests) and suggest that a combination of informative molecular, serological, and ecological data is a helpful tool to understand the molecular epidemiology of arboviruses.